Boondoggled: A Case Report of Arts and Crafts Gone Wrong - Fumo, David Eugene (Translation: The University of Toledo Journal of Medical Sciences, 2019)
Self-insertion of foreign bodies into the urinary tract is a not-uncommon urological problem with significant psychosocial implications. A 12-year-old male presented to the ED when his father noted blood in the patient’s urine. During evaluation, the patient admitted to inserting Boondoggle, a plastic arts and crafts string, into his urethra 1 week prior. He admitted to performing this activity on multiple prior occasions. He subsequently developed worsening frequency, urgency, dysuria, hematuria, and suprapubic pain. Bladder ultrasound and KUB were obtained which demonstrated a large amount of hyperdense material coiled in the bladder. He was brought to the OR the following day for removal of the foreign body. After failed attempts at endoscopic retrieval, 34 feet of plastic string was removed via an open approach. The bladder was closed and a foley was left in place. He was discharged on postoperative day 2 on culture specific antibiotics after a successful void trial. Urethral masturbation has been associated with psychiatric disorders, fetishism, and sadomasochistic tendencies. For the urologist, it is critical to recognize the mental health issues portended by urethral foreign body insertion, and take the appropriate steps to address the underlying problem.